Suspensions of mixed oxide nanoparticles

A cerium and zirconium mixed oxide nanoparticle suspension addresses the challenges of CGPFs by enhancing catalytic activity and thermal resistance, effectively reducing fine particles and pollutants while minimizing back pressure.

JP7626759B2Active Publication Date: 2025-02-04RHODIA OPERATIONS SAS
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022520015
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-01
Filing Date
2020-09-28
Publication Date
2025-02-04
Estimated Expiration
2040-09-28

AI Technical Summary

Technical Problem

Existing technologies for gasoline fine particle filters (CGPF) face challenges in efficiently reducing fine particles and pollutants under varying operating conditions, particularly due to the difficulty in coating narrow porous filters and maintaining high thermal resistance while minimizing back pressure.

Method used

A suspension of cerium and zirconium mixed oxide nanoparticles is used in a water-based medium with specific pH and surface area characteristics, allowing for easy processing and application in CGPFs, enhancing catalytic activity and thermal resistance.

Benefits of technology

The suspension enables effective reduction of fine particles and pollutants by maintaining high thermal resistance and minimizing back pressure, optimizing engine efficiency and reducing emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626759000001
    Figure 0007626759000001
Patent Text Reader

Abstract

The present invention relates to a suspension of nanoparticles of mixed oxides based on cerium and zirconium.The invention also relates to the use of said suspension for the preparation of catalyzed gasoline particulate filters.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to European Patent Application No. 19315119.8, filed October 1, 2019, the contents of which are incorporated herein by reference in their entirety for all purposes. In the event of any discrepancy between this application and this European application that would affect the clarity of a term or phrase, reference should be made solely to this application.

[0002] The present invention relates to a suspension of nanoparticles of mixed oxides based on cerium and zirconium. The present invention also relates to the use of said suspension for the preparation of a catalyzed gasoline particulate filter (cGPF).

[0003] With current legislation in Europe and China requiring compliance with particle number (PN) limits, particulate filters are being applied for gasoline engines, especially for gasoline direct injection technology (GDI). It is advantageous to combine catalytic activity for the conversion of gaseous pollutants with particulate reduction in one step. This can be achieved with catalyzed gasoline particulate filters (cGPFs). As a result of this, cGPFs have been developed and provide an effective route to reduce particle numbers and pollutants under all driving conditions. cGPFs are also an efficient means to optimize the aftertreatment layout with a reduction in the number of catalytic components in the exhaust line.

[0004] The working principle of the cGPF is comparable to the well-established catalyzed diesel particulate filter (cDPF). Particles are removed from the exhaust gas by physical filtration using a honeycomb structure similar to an exhaust gas catalyst substrate, but with channels blocked at alternate ends. The exhaust gas is thus forced to flow through the porous walls between the channels, and particles are deposited on and in the walls. A catalytic coating provides three-way catalytic (TWC) activity and removes carbon monoxide (CO), unburned hydrocarbons (HC) and nitrogen oxides (NO x) at the same time. The TWC coating also helps soot to burn in the cGPF. Filter substrates for gasoline engines are typically made of cordierite, but other substrate compositions such as silicon carbide or aluminum titanate are also possible without any limitation of the present invention. Compared to cDPFs, the particle size distribution in gasoline exhaust gas is different (shifted towards smaller particles) as a result of the need for narrower porosity filters. It is well known that coating narrow porosity filters is difficult but rewarding, since back pressure must be minimized to limit the negative impact on engine efficiency, fuel economy and CO2 emissions. The temperature of the exhaust gas for gasoline engines is generally higher than for diesel engines - as a result of the average operating temperature being typically higher for cGPFs. This higher temperature also allows easier regeneration of the filter compared to diesel. Thanks to the presence of the TWC washcoat, a portion of the soot can be burned continuously. Periodic cDPF regeneration triggers the complete burning of the soot.

[0005] Preparation of cGPFs usually involves the following steps: contacting a porous filter substrate with a dispersion of a catalyst composition; drawing the catalyst composition into the channels of the filter substrate by application of a vacuum; drying and calcining the coated filter substrate. The dispersion is typically made by mixing a solution of precious metals (preferably platinum, palladium and / or rhodium) with mixed oxides based on cerium and zirconium, alumina and other inorganic and organic components.

[0006] Mixed oxides based on cerium and zirconium are usually commercialized in solid form. Moreover, the preparation of catalyst dispersions requires an additional step of dispersing the mixed oxides in a liquid. Therefore, there is a need for a suspension of said mixed oxides in a liquid medium that can be used directly for the preparation of catalyst dispersions. The suspension of the mixed oxides must exhibit a compromise of properties so that it can be easily used and processed during the preparation of catalyst dispersions. In particular, said suspension must exhibit a viscosity that is suitable for the preparation of catalyst dispersions and for use to prepare cGPFs. The percentage of solids in the suspension should also be high enough for convenient use and productivity.

[0007] The properties of the mixed oxide also affect the performance of the cGPF. For example, to reduce the backpressure increase due to the presence of the washcoat on the filter, the washcoat should be placed as uniformly as possible within the filter. The mixed oxide particles should also be impregnated into the filter while maintaining a high thermal resistance.

[0008] The suspension of the present invention aims to achieve such a compromise. [Background technology]

[0009] WO 2017 / 056067 discloses cGPFs prepared with a catalyst dispersion with a d50 of about 5 μm.

[0010] Although US Pat. No. 8,173,087 discloses a catalyst dispersion, it does not disclose the suspension of the present invention.

[0011] US Pat. No. 10,207,253 B1 discloses a catalyst composition comprising particles of CeO2 and ZrO2, which may be in the form of separate nanoparticles.

[0012] There is no disclosure of mixed oxides based on cerium and zirconium.

[0013] WO 2006 / 030120 discloses mixed oxides used to coat filters. It does not disclose suspensions as claimed.

[0014] US Patent No. 7,713,908 discloses a suspension of metal oxide powders with diameters of 50 nm or less, the pH of which can be between 5 and 9 for combinations of mixed oxides based on cerium and zirconium and alumina.

[0015] WO 2017 / 187086 discloses mixed oxides based on cerium and zirconium. WO 2017 / 187086 specifies that the mixed oxides can be ground to a D50 of 500 nm to 50,000 nm, but there is no mention of a suspension or any acid. For weathering tests with rhodium using a suspension, the D50 is 1000 nm to 20,000 nm and is therefore outside the claimed range. WO 2017 / 187086 therefore does not disclose a suspension as claimed.

[0016] The calcinations, more particularly the calcinations for which values ​​of specific surface area or porosity after calcination are given, are calcinations in air, unless otherwise stated. For the continuation of the present description, it is also stated that in the range values ​​given, the limit values ​​are included, unless otherwise stated. This also applies to expressions including "at least" or "at most". Summary of the Invention

[0017] The present invention relates to a suspension of particles as disclosed in any one of claims 1 to 34. The suspension comprises particles of at least one mixed oxide of zirconium, of cerium, optionally of lanthanum and optionally of at least one rare earth element other than cerium and lanthanum (reference RE), in an aqueous liquid medium comprising an acid, which is either a mineral acid or a carboxylic acid containing from 2 to 12 carbon atoms, preferably from 2 to 8 carbon atoms, the suspension having the following characteristics: the pH of the suspension is between 2.0 and 7.0 (this latter value being excluded), more particularly between 3.0 and 6.0; the proportion of the mixed oxide is between 20.0% and 50.0% by weight, more particularly between 25.0% and 50.0% by weight, even more particularly between 30.0% and 45.0% by weight or between 35.0% and 45.0% by weight; - The specific surface area of ​​the suspension is 15 m when the mixed oxide does not contain La or RE. 2 / g, and 21m when the mixed oxide contains La and / or RE. 2 / g, the specific surface area being measured after calcination of the solid isolated from the suspension in air at 1100 °C for 4 h; where: the particles of the mixed oxide exhibit a D50 of 20.0 nm to 900 nm, more particularly 20.0 nm to 800.0 nm, more particularly 20.0 nm to 500.0 nm, even more particularly 20.0 nm to 400.0 nm, even more particularly 20.0 nm to 300.0 nm or 20.0 nm to 200.0 nm or 20.0 to 100.0 nm; - The proportions of the elements Ce, Zr, La and RE, expressed by weight of oxides relative to the mixed oxide, are as follows: 20.0% to 55.0% by weight of cerium; not more than 10.0% by weight of lanthanum; · 15.0% by weight or less of rare earth elements (RE) other than cerium and lanthanum; The remainder as zirconium That is, has.

[0018] The present invention relates to the following: particles of at least one mixed oxide of zirconium, of cerium, optionally of lanthanum and optionally of at least one rare earth element (RE) other than cerium and lanthanum; · Aqueous liquid medium; An acid which is either a mineral acid or a carboxylic acid containing from 2 to 12 carbon atoms, preferably from 2 to 8 carbon atoms. A suspension comprising: The suspension has the following characteristics: the pH of the suspension is between 2.0 and 7.0 (this latter value being excluded), more particularly between 3.0 and 6.0; the proportion of the mixed oxide is between 20.0% and 50.0% by weight, more particularly between 25.0% and 50.0% by weight, even more particularly between 30.0% and 45.0% by weight or between 35.0% and 45.0% by weight; - The specific surface area of ​​the suspension is 15 m when the mixed oxide does not contain La or RE. 2 / g, and 21m when the mixed oxide contains La and / or RE. 2 / g, the specific surface area being measured after calcination of the solid isolated from the suspension in air at 1100 °C for 4 h; where: the particles of the mixed oxide exhibit a D50 of 20.0 nm to 900 nm, more particularly 20.0 nm to 800.0 nm, more particularly 20.0 nm to 500.0 nm, even more particularly 20.0 nm to 400.0 nm, even more particularly 20.0 nm to 300.0 nm or 20.0 nm to 200.0 nm or 20.0 to 100.0 nm; - The proportions of the elements Ce, Zr, La and RE, expressed by weight of oxides relative to the mixed oxide, are as follows: 20.0% to 55.0% by weight of cerium; not more than 10.0% by weight of lanthanum; · 15.0% by weight or less of rare earth elements (RE) other than cerium and lanthanum; The remainder as zirconium That is, The present invention relates to a suspension having the formula:

[0019] The invention also relates to a method for the preparation of a suspension as disclosed in any one of claims 35 to 37. According to this method, a dispersion comprising the mixed oxide M dispersed in an aqueous liquid medium containing an acid is subjected to a mechanical treatment in order to reduce the size of the particles of the mixed oxide.

[0020] The invention also relates to the use of the suspension for the preparation of a cGPF as disclosed in claim 38, and to a process for the preparation of a catalyst composition, in which the suspension is contacted with at least an inorganic material and optionally at least one PGM as disclosed in any one of claims 39 to 41.

[0021] More specific details regarding these inventions are given below. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The term "suspension" means a liquid medium in which solid particles are dispersed.

[0023] The suspension comprises, in an aqueous liquid medium, at least one mixed oxide of zirconium, of cerium, optionally of lanthanum and optionally of at least one rare earth element (RE) other than cerium and lanthanum. The proportion of the mixed oxide in the suspension is between 20.0% and 50.0% by weight, more particularly between 25.0% and 50.0% by weight, even more particularly between 30.0% and 45.0% or between 35.0% and 45% by weight. This proportion in % is expressed as the weight of the mixed oxide relative to the total weight of the suspension. For example, a proportion of 40.0% by weight of the mixed oxide corresponds to 40.0 g of the mixed oxide per 100.0 g of the suspension.

[0024] The mixed oxide according to the invention is primarily characterized by the nature and proportions of its constituents. The mixed oxide is based on the elements Ce, Zr, optionally La and optionally at least one RE. For example, the mixed oxide may be based on the elements Ce and Zr; on the elements Ce, Zr and La or on the elements Ce, Zr, La and RE.

[0025] The proportion of cerium in the mixed oxide may vary within wide limits. In practice, the proportion of cerium is between 20.0% and 55.0% by weight. This proportion may be between 30.0% and 55.0% by weight, more particularly between 30.0% and 45.0% by weight. This proportion may also be between 25.0% and 35.0% by weight.

[0026] The proportion of lanthanum in the mixed oxide is less than or equal to 10.0% by weight, which may be between 0% and 10.0% by weight, more particularly between 1.0% and 10.0% by weight.

[0027] The mixed oxide may also contain at least one rare earth element (RE) other than cerium and other than lanthanum. RE denotes a rare earth element other than cerium or lanthanum. The RE may be selected in the group consisting of dysprosium (Dy), erbium (Er), europium (Eu), gadolinium (Gd), holmium (Ho), lutetium (Lu), neodymium (Nd), praseodymium (Pr), promethium (Pm), samarium (Sm), scandium (Sc), terbium (Tb), thulium (Tm), ytterbium (Yb) and yttrium (Y). The RE may more particularly be selected in the group consisting of Nd, Y and Pr. The mixed oxide may contain at least one or two rare earth elements other than cerium and other than lanthanum. The total proportion of rare earth elements other than cerium and lanthanum is less than or equal to 15.0% by weight, more specifically less than or equal to 10.0% by weight.

[0028] The mixed oxide may also contain the element hafnium. In fact, this element is usually present in combination with zirconium in the ores in which it occurs in the natural state. The relative proportion of hafnium to zirconium depends on the ore from which it is extracted. The relative proportion Zr / Hf by weight in some ores may be about 50 / 1. Baddeleyite therefore contains approximately 98% ZrO2 and 2% HfO2. The proportion of hafnium is less than 2.5% or even less than 2.0% by weight.

[0029] The above-mentioned elements are generally present in the mixed oxide as oxides. However, they may also be partially present in the form of hydroxides or oxyhydroxides. Thus, the elements Ce and Zr, and, if any, La or RE, and, if any, Hf, are present in the mixed oxide as oxides, but they may also be present in the mixed oxide as oxides and also partially in the form of hydroxides or oxyhydroxides.

[0030] As is customary in the field of mixed oxides, the proportions of the elements are given by weight of the oxide relative to the mixed oxide as a whole. For the calculation of these proportions, the following oxides are taken into account: CeO2, ZrO2, HfO2, La2O3; Pr6O 11 RE2O3 for all RE except Pr, where Pr is taken into account. Thus, as an example, a proportion of 20.0% by weight of cerium means a proportion of 20.0% by weight of CeO2 in the mixed oxide. The proportions of the elements are determined by conventional analytical methods such as X-ray fluorescence analysis or by inductively coupled plasma mass spectrometry.

[0031] The mixed oxide of the present invention comprises the above-mentioned elements in the above-mentioned proportions, but it may also additionally comprise other elements, such as impurities. The impurities may originate from the raw materials or starting materials used in the process of preparing the mixed oxide. The total proportion of impurities may generally be less than or equal to 0.25% by weight (≦0.25% by weight), more particularly less than or equal to 0.20% by weight (≦0.20% by weight), based on the mixed oxide.

[0032] Zirconium oxide is the remainder of the composition. The weight percentage of zirconium is the remainder of the mixed oxide to 100% of the other elements (Ce, La, RE if present, Hf if present). The percentage of zirconium in the mixed oxide is typically greater than 35.0% by weight, more specifically greater than 45.0% by weight, even more specifically greater than 50.0% by weight. The percentage of zirconium is typically less than 79.0% by weight.

[0033] According to an embodiment, the mixed oxide exhibits a weight ratio ZrO2 / CeO2 greater than 1.0, typically greater than 1.5.

[0034] The aqueous liquid medium contains an acid, which is either a mineral acid or a carboxylic acid containing 2 to 12 carbon atoms, preferably 2 to 8 carbon atoms. The mineral acid is, for example, nitric acid. The proportion of the acid, expressed as the weight of the acid with respect to the total suspension, is between 0.01% and 10.0% by weight, more particularly between 0.5% and 6.0% by weight, depending on the acid used.

[0035] According to an embodiment, the suspension does not contain any metal oxide other than the mixed oxides disclosed above. A metal oxide is defined as an oxide of at least one metal. The metal is more particularly selected in the group consisting of Al, Zr or Ti. The metal oxide can be, for example, alumina, zirconia or titania.

[0036] The suspension is also characterized by a high specific surface area. The specific surface area (BET) of the suspension is 15 m when the mixed oxide does not contain La or RE. 2 / g, the specific surface area being measured after calcination of the solid isolated from the suspension in air at 1100 °C for 4 hours. This is the case for mixed oxides of cerium and zirconium. The specific surface area (BET) of the suspension is 21 m when the mixed oxide contains La and / or RE. 2 / g, the specific surface area being measured after calcination of the solid isolated from the suspension in air at 1100 °C for 4 hours. This is the case, for example, for mixed oxides of cerium, zirconium and lanthanum or mixed oxides of cerium, zirconium, lanthanum and at least one rare earth other than cerium and lanthanum. In both cases, this specific surface area is generally greater than 40 m 2 / g or less, more specifically 35m 2 / g or less, and more specifically 30m 2 / g or less.

[0037] After calcination at 1000°C for 4 hours in air, the suspension also had a concentration of at least 35m2 / g, more specifically at least 40m 2 The specific surface area (BET) is given in g / g, measured after calcination of the solid isolated from the suspension in air at 1000 °C for 4 hours. This specific surface area is generally 70 m 2 / g or less, more specifically 65m 2 / g or less, and more specifically 60m 2 / g or less.

[0038] According to a particular embodiment, the specific surface area of ​​the suspensions at 1100° C. and 1000° C. disclosed above is measured on the solid isolated by the following method comprising the steps: (i) a step in which a solid is isolated from the suspension; (ii) the solid is then dried in air at 500°C for 1 hour; (iii) The dried solid is calcined in air at 1100°C for 4 hours or at 1000°C for 4 hours, respectively.

[0039] Thus, the following steps are performed on the suspension to measure the specific surface area at 1100° C. / 4 h or at 1000° C. / 4 h, respectively: (i)→(ii)→(iii)→measurement of the specific surface area (BET).

[0040] For the sake of clarity, the expression "specific surface area (BET) of the suspension" therefore refers to the specific surface area (BET) of the solid (mixed oxide) isolated from the suspension.

[0041] The term "specific surface area (BET)" is understood to mean the BET specific surface area measured by nitrogen adsorption. The specific surface area is well known to those skilled in the art and is measured according to the Brunauer-Emmett-Teller method. The theory of this method was first described in the periodical "The Journal of the American Chemical Society, 60, 309 (1938)". More detailed information on this theory can also be found in chapter 4 of "Powder surface area and porosity", 2nd edition, ISBN 978-94-015-7955-1. The method of nitrogen adsorption is disclosed in the standard ASTM D 3663-03 (reapproved in 2008). In practice, the specific surface area (BET) can be measured automatically using the instrument Flowsorb II 2300 or the instrument Tristar 3000 from Micromeritics according to the constructor's guidelines. They can also be measured automatically using a Mountech Macsorb analyzer model I-1220 following the constructor's guidelines. Prior to measurement, the samples are degassed, optionally under vacuum, by heating at temperatures up to 300° C. to remove adsorbed volatile species. More specific conditions can be found in the examples.

[0042] The suspension may also exhibit a specific porosity, measured by mercury porosimetry. In fact, the suspension may also exhibit a pore volume, measured by mercury porosimetry (referred to as PV) for pores with a diameter of less than 300 nm, of greater than 0.15 mL / g, more particularly greater than 0.25 mL / g. 0~300nm ) can be shown. PV 0~300nm can be 0.15 to 0.80 mL / g.

[0043] The suspension may also exhibit a total pore volume of greater than 0.50 mL / g, more specifically greater than 0.60 mL / g. The TPV may be from 0.50 to 2.00 mL / g, more specifically from 0.50 to 1.50 mL / g, and even more specifically from 0.50 to 1.30 mL / g.

[0044] According to certain embodiments, the pore volume disclosed above can be determined by the following steps: (i) a step in which the solid is isolated; (ii) the solid is dried in air at 500° C. for 1 hour; It is measured according to.

[0045] Thus, the following steps: (i)→(ii)→Measurement of porosity are carried out on the suspension to measure the porosity.

[0046] With respect to the specific surface area, the pore volume therefore refers to the pore volume of the solid (mixed oxide) isolated from the suspension.

[0047] The above disclosed method for the measurement of the specific surface area and of the pore volume comprises a step (i) in which the solid is isolated from the suspension. Step (i) is conveniently carried out by filtration. In step (ii), the solid isolated from step (i) is dried in air at 500° C. for 1 hour. Step (ii) serves to remove the remains of the aqueous liquid medium containing the acid. After the drying step (ii), the solid may form small pieces which may be conveniently deagglomerated. Deagglomeration is conveniently carried out using a mortar.

[0048] Mercury porosimetry is a standard technique used in the field of porous catalysts and consists in the progressive intrusion of mercury into the pores of a porous structure under controlled pressure. The porosity is measured by mercury intrusion according to techniques well known in the art. The porosity can be measured using a Micromeritics V 9620 Automatic Mercury Porosimeter, following the constructor's guidelines. The porosimeter includes a powder hardness tester. The method is based on the determination of the pore volume as a function of the pore size (V=f(d), where V means pore volume and d means pore diameter). From this data it is possible to obtain the curve (C) giving the derivative dV / dlogD. From the curve (C), the pore volume PV 0~300nmand the total pore volume TPV (both measured after calcination at 500° C. in air for 1 hour) are determined. The procedures given in the examples are preferably followed.

[0049] The mixed oxide is in the form of particles exhibiting a D50 of 20.0 nm to 900 nm, which may be more specifically 20.0 nm to 800.0 nm, more specifically 20.0 nm to 500.0 nm, even more specifically 20.0 nm to 400.0 nm, even more specifically 20.0 to 300.0 nm or 20.0 nm to 200.0 nm or 20.0 to 100.0 nm.

[0050] The particles preferably exhibit a D90 of less than 1000 nm. The D90 may be more specifically between 50 nm and 1000 nm, more specifically between 50 nm and 700 nm, even more specifically between 50 nm and 500.0 nm. The D90 is preferably less than 200 nm or even less than 100 nm.

[0051] According to one embodiment, the suspension exhibits a D50 between 20 nm and 100 nm and a D90 between 50 nm and 120 nm.

[0052] According to another embodiment, the suspension exhibits a D50 between 40 nm and 100 nm and a D90 between 50 nm and 120 nm.

[0053] D50 and D90 are determined from the particle size distribution (in volume units) obtained using a laser diffraction particle size analyzer. D50 and D90 have their usual meanings as used in the field of particle size analysis. See, for example, https: / / www.horiba.com / fileadmin / uploads / Scientific / Documents / PSA / PSA_Guidebook.pdf. D50 (median) is defined as the size value corresponding to the cumulative distribution at 50%. Similarly, D90 is defined as the size value corresponding to the cumulative distribution at 90%.

[0054] D50 and D90 can be determined using a Beckman Coulter LS 13320 laser diffraction particle size analyzer (Beckman coulter, Inc.) using standard procedures predefined by the instrument software. The Fraunhofer mode can be used according to the constructor's guidelines (https: / / www.beckmancoulter.com / wsrportal / techdocs?docname=B05577AB.pdf). A relative refractive index of 1.6 is used. The method disclosed in the examples can be used conveniently.

[0055] The suspension also contains an acid, which is either a mineral acid or a carboxylic acid containing 2 to 12 carbon atoms, preferably 2 to 8 carbon atoms. The mineral acid may more particularly be nitric acid. The carboxylic acid may also contain at least one functional group other than COOH. The functional group may be selected in the group consisting of OH, C=O, anhydride and ester groups. The carboxylic acid may be a mono-, di- or tri-carboxylic acid or an alpha-hydroxy-carboxylic acid. The carboxylic acid may more particularly be a compound of the formula R 1 -COOH(where R 1 is a straight or branched alkyl group containing 1 to 11, more particularly 1 to 7 carbon atoms. More particularly, the carboxylic acid may be selected from the group consisting of acetic acid, propionic acid, butanoic acid, hexanoic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, maleic acid and citric acid. The carboxylic acid is typically acetic acid.

[0056] The aqueous liquid medium comprises water. According to an embodiment, water is the main component of the liquid medium. The aqueous liquid medium can be, for example, water.

[0057] According to another embodiment, the aqueous liquid medium may contain at least one other liquid that is miscible with water. The other liquid may be, for example, an organic liquid such as an alcohol, an ester or a ketone. The nature and amount of the other liquid should preferably be such that it does not affect the stability of the suspension. The weight ratio water / other liquid is preferably 100 / 0-80 / 20, more preferably 100 / 0-90 / 10, even more preferably 100 / 0-95 / 5.

[0058] The aqueous liquid medium may also contain an acid. It may also contain impurities present in the mixed oxide to be mechanically treated. The impurities may be released during the mechanical treatment.

[0059] The pH of the suspension is between 2.0 and 7.0, with the latter value being excluded (2.0≦pH<7.0). The pH of the suspension may in particular be between 3.0 and 6.0. It has been observed that the pH influences the ability to reduce the attainment of the claimed values ​​of D50 and D90 and also the viscosity of the suspension.

[0060] The suspension typically exhibits a viscosity V that is less than 1000 cP, more specifically less than 500 cP, and even more specifically less than 100 cP. V is measured at 20° C. using a rheometer employing a cylindrical couette geometry. The sample is first heated at 1 s over a 5 minute ramp time. -1 From 100s -1 and then at an increasing shear rate of 100 s for 5 min. -1 From 1s -1 The viscosity value retained (V) is measured over a period of 10 s during the shear rate reduction. -1 The value is measured at a shear rate of 100 / s.

[0061] As regards the use of the suspension according to the invention, this falls within the field of motor vehicle pollution control catalysis. The suspension according to the invention can be used for the preparation of cGPF.

[0062] A cGPF is typically formed from a porous substrate and a coating comprising a mixed oxide applied on at least a portion of the porous substrate. The coating can be made of one or more layers, with at least one layer being made of a catalytic composition comprising a mixed oxide. The coating layer is made of a catalytic composition similar to that used in TWC technology.

[0063] Preparation of a cGPF typically involves the following steps: (i) contacting a porous filter substrate with an aqueous dispersion of a catalyst composition; drawing the catalyst composition into the channels of the filter and / or into the porous substrate, preferably by application of a vacuum; and drying and calcining the coated filter.

[0064] About porous substrates The porous substrate is usually made of a ceramic-like material such as, for example, cordierite, silicon carbide, silicon nitride, zirconia, mullite, spodumene, alumina-silica-magnesia, zirconium silicate, and / or aluminum titanate, typically cordierite or silicon carbide. The porous substrate may be quite similar to substrates typically used in exhaust gas treatment systems for gasoline engines. For example, the porous substrate may exhibit a conventional honeycomb structure.

[0065] The filter may take the form of a "through-flow filter" or a "wall-flow filter" (WFF). The filter is preferably a wall-flow filter. Wall-flow filters operate by forcing the flow of exhaust gas (including particulate matter) through a wall formed of a porous material.

[0066] A wall flow filter typically has a first surface and a second surface defining a longitudinal direction therebetween, in use one of the first and second surfaces will be an inlet surface for the exhaust gas and the other will be an outlet surface for the treated exhaust gas.

[0067] Wall flow filters typically have a first and a second plurality of channels extending longitudinally. The first plurality of channels is open at a first surface and closed at a second surface. The second plurality of channels is open at a second surface and closed at a first surface. The channels are preferably parallel to each other to provide a constant wall thickness between the channels. As a result, gas entering one of the plurality of channels cannot exit the monolith without diffusing through the channel wall into the other of the plurality of channels. The channels are closed with the introduction of a sealant material into the open end of the channel. Preferably, the number of channels in the first plurality is equal to the number of channels in the second plurality, each plurality being uniformly distributed throughout the monolith. The channels can have a cross-section that is rectangular, square, circular, oval, triangular, hexagonal, or other polygonal in shape.

[0068] The substrate is often made of cordierite and exhibits minimal porosity to accommodate the preparation of efficient cGPFs with low backpressure.

[0069] Catalyst Composition A coating (commonly known as a "washcoat") is applied onto at least a portion of the substrate. The coating layer is formed from a catalyst composition prepared from a suspension of the present invention. Typically, the catalyst composition is prepared by contacting a suspension of the present invention and at least one inorganic material and optionally at least one PGM. The catalyst composition is thus typically (i) A mixed oxide (as defined above); (ii) at least one inorganic material; (ii) optionally at least one PGM; Includes.

[0070] The inorganic material can be selected from the group consisting of optionally doped alumina, titanium oxide, cerium oxide, zirconium oxide, silica, spinel, zeolites, silicates, crystalline silico-aluminum phosphates and crystalline aluminum phosphates. The composition can also include other additives specific to each formulation: H2S scavengers, organic or inorganic modifiers that serve to facilitate coating, colloidal alumina, etc. The coating also includes at least one dispersed platinum group metal (PGM), more specifically selected from the group consisting of Pt, Rh or Pd. The PGM is generally in the form of a salt, for example in the form of a nitrate.

[0071] The present invention therefore also relates to a method for preparing a catalyst composition, in which the suspension of the present invention is contacted with at least one inorganic material and optionally at least one PGM. The inorganic material can be in the form of a solid or a dispersion in an aqueous liquid medium. Since the proportion of mixed oxides in the suspension is usually already high, the inorganic material is preferably in the form of a dispersion in an aqueous liquid medium. In addition, the method for preparing the catalyst composition usually includes the addition of a liquid, preferably water, to ensure good mixing of the components of the catalyst composition.

[0072] The PGMs may be in the form of a solid or an aqueous solution.

[0073] The role of the coating is to convert, by chemical reactions, certain pollutants in the exhaust gases, in particular carbon monoxide, unburned hydrocarbons and nitrogen oxides, into products that are less harmful to the environment. The chemical reactions involved can be: 2CO+O2→2CO2 2NO+2CO→N2+2CO2 4C x H y +(4x+y)O2 → 4×CO2+2yH2O

[0074] The suspension of the present invention may also be used for the preparation of catalytic converters.

[0075] Method for preparing the suspension The suspensions of the present invention are prepared by a method in which a dispersion comprising the mixed oxide M dispersed in an aqueous liquid medium containing an acid is subjected to a mechanical treatment to reduce the size of the particles of the mixed oxide.

[0076] Preparation of Mechanically Treated Dispersions The mechanically treated mixed oxide M can have the same composition as the mixed oxide of suspension.It can also have substantially the same composition as the mixed oxide of suspension.The mixed oxide M should preferably exhibit a D90 of less than 100 μm, more particularly less than 60 μm, even more particularly less than 50 μm.

[0077] Due to the reduction in specific surface area induced by the mechanical treatment, in order for the specific surface area of ​​the suspension to be within the claimed values, the mixed oxide M should exhibit a specific surface area typically higher than the claimed values. The specific surface area of ​​the mechanically treated mixed oxides is - 17m if the mixed oxide M does not contain La or RE 2 / g, preferably 20m 2 / g; - 25m if the mixed oxide contains La and / or RE 2 / g, preferably 27m 2 / g, This specific surface area is measured after calcination of the mixed oxide in air at 1100° C. for 4 hours.

[0078] The mixed oxide M may be prepared according to the teachings of WO 2011 / 138255, WO 2016 / 037059, WO 2017 / 072509, EP 1527018 or EP 1621251. A convenient technique disclosed in EP 1527018 comprises the following steps: a) preparing a mixture comprising a sol of a cerium, lanthanum and optionally RE compound and a zirconium compound; b) adding a solution of a basic compound to the mixture of step a), thereby obtaining a precipitate; c) heating the precipitate in an aqueous medium; d) calcining the precipitate thus obtained in step c); Includes.

[0079] More specifically, for the preparation of the mixed oxide M, more specifically the mixed oxide comprising La and RE, the recipe of the example of EP 1 527 018 can be followed or modified.

[0080] Another convenient technique disclosed in WO2017185224 comprises the following steps: a) an aqueous solution containing at least a zirconium chloride salt, a cerium salt, and optionally at least one rare earth salt other than cerium and other than lanthanum, said aqueous solution containing sulfate anions (SO 2- reacting said aqueous solution containing 1,2-dichlorophenyl ether with a basic compound to form a precipitate; b) separating the precipitate from the liquid medium; c) heating the precipitate obtained in step b) in an aqueous medium; d) adding a lanthanum salt, optionally together with a basic compound; e) adding lauric acid; f) separating the precipitate from the liquid medium; g) calcining the precipitate; Includes.

[0081] More specifically, for the preparation of the mixed oxides M, more specifically mixed oxides comprising La and / or RE, the recipes disclosed in the examples of WO 2017 / 185224 can be followed or modified.

[0082] The dispersion is prepared by dispersing the mixed oxide M in an aqueous liquid medium containing an acid. The pH of the resulting dispersion is then optionally adjusted by adding an acid or a base. The pH of the dispersion is substantially the same as the pH of the final suspension. It is customary to prepare the dispersion by adding the mixed oxide M in powder form to an aqueous liquid medium containing an acid under vigorous stirring to obtain a homogeneous dispersion.

[0083] The dispersion of mixed oxide M is subjected to mechanical treatment to reduce the size of the particles. A device is used that provides sufficient energy / shear to reduce the size of the particles without significantly affecting the specific surface area. The particles of the mixed oxide are considered to be in the form of primary particles or agglomerates that are broken into smaller aggregates of primary particles. The device should also provide good mixing to ensure uniform processing of the dispersion. The device can be a high pressure homogenizer, wet jet mill, agitator bead mill, high shear agitator, ultrasonic homogenizer.

[0084] High pressure homogenizers (HPH) consist in forcing a dispersion through a narrow gap (e.g. a nozzle with a diameter of 0.1-0.2 mm) at high pressures, around 1500-4000 bar, and then relaxing the dispersion through this nozzle to atmospheric pressure. The dispersion is then subjected to turbulence which causes very high shear stresses, cavitation and deagglomeration of the clumps. The shear is induced by the sudden restriction of the flow through the restrictive nozzle.

[0085] The wet jet milling technique shows some similarities with the HPH technique. In wet jet milling, the dispersion is compressed in a chamber, usually at 1500-2500 bar, and split into two streams, which pass through two respective nozzles with a diameter of 0.1-0.2 mm. The dispersion then leaves the nozzles at atmospheric pressure forming two jets of liquid. The two nozzles are in opposite positions and the two jets collide with each other at high speed. The collision generates high shear stresses on the particles, causing their deagglomeration. This technique and the HPH are better adapted to primary particles below 60 μm and dispersion viscosities below 5000 cP.

[0086] The agitator bead mill technology is based on the grinding of a solid with hard beads that are in contact with the solid and move at high speed. The beads are often made of a hard material such as zirconia. The beads preferably exhibit a diameter that is less than 500 μm, more specifically between 50 and 500 μm, even more specifically between 200 and 500 μm. The smaller the diameter, the more the beads can be added in contact with the solid; it makes it possible to obtain more collisions between the beads and the particles of the solid. More details regarding this technology can be found in the examples. The skilled person will be able to obtain the suspension as claimed using the wet milling conditions disclosed in the examples. The agitator bead mill consists of a grinding vessel containing the beads and a means for moving the beads inside the vessel. The said means ensures vigorous movement of the beads inside the vessel. Various agitator bead mills available on the market can be used in the process of the invention. The agitator bead technology was conveniently used for the preparation of the suspension disclosed in the examples. EXAMPLES

[0087] Specific surface area (BET) The surface area was measured by the BET flow method (multi-point) with N2 adsorption at liquid N2 temperature (77K) using a Micromeritics TRISTAR 3020 analyzer. The specific surface area was calculated by the well-known Brunauer-Emmett-Teller (BET) method. Before the measurement, the sample was pretreated in a vacuum oven at 300 °C for 15 minutes to remove any residual moisture and adsorbed species.

[0088] As discussed above, the specific surface area (BET) of the suspension is measured for the solid isolated from the dispersion system.

[0089] Mercury porosimetry The pore volume was measured using a Micromeritics Autopore IV 9500 Automatic Mercury Porosimeter according to the constructor's guidelines. A value of 130° was used for the contact angle (θ), and the surface tension of mercury was fixed at 480 dyne / cm. A vacuum was applied to the sample up to 50 μmHg. Mercury intrusion curves were collected in the pressure range from 0.98 Psi to 30 Psi for the low-pressure slots and from 30 Psi to 60000 Psi for the high-pressure slots; this enables the analysis of a wide range of pores, typically with diameters from 3 nm to 200 μm.

[0090] Particle size analysis A laser particle size analyzer was used. A relative refractive index of 1.6 was used. The suspension (approximately 10 g) was diluted in an aqueous solution (60 mL) at the same pH as the pH of the suspension. After sonication (5 minutes; 45 kHz) of the diluted suspension in an external ultrasonic bath, the diluted suspension was introduced into the measurement cell. It is preferable to perform the measurement with PIDS (polarization intensity microdispersion scattering) in the range of 45% to 55% (45% < PIDS < 55%).

[0091] Viscosity of the suspension A Malvern Kinexus Pro+ stress-controlled rheometer using cylindrical cup geometry was used. The rheology of the suspension was measured at 20 °C. The sample was first subjected to 1 s -1 to 100 s over a ramp time of 5 minutes-1 and then at an increasing shear rate of 100 s for 5 min. -1 From 1s -1 The viscosity values ​​(V) were measured at 100 s -1 From 1s -1 During the reduction of the shear rate up to 10 s -1 The value is measured at a shear rate of 100 / s.

[0092] XRD X-ray powder diffraction patterns were acquired on an X'pertPro MPD powder diffractometer (PANAlytical Company) equipped with a Cu Kα (1.5406 Å) radiation source and a linear detector X Celerator Detector. Scattering intensity data were collected from 2θ values ​​between 19 and 85° by scanning in 0.017° steps with a counting time of 28 s at each step. Crystalline phases were identified by matching with the International Centre for Diffraction Data Powder Diffraction File (ICDD-PDF). The average crystallite size (D) of the sample was determined with the help of the Scherrer equation from the line broadening taking into account the instrument width. XRD ) was determined and the intensity of the most prominent peak (111) was used to estimate the lattice parameters by the standard cubic indexation method.

[0093] For all Examples 1 to 6 and Comparative Examples 1 to 2, the starting materials had the following specific surface area: 29 m2 after calcination at 1100° C. in air for 4 hours. 2A mixed oxide M was used with the following composition (% expressed by weight of oxide), characterized in / g: Zr / Ce / La 58.5% / 36.0% / 5.5%. This mixed oxide was prepared according to the teachings of EP 1527018 B1. The powder of mixed oxide M used in the examples initially exhibits a D50 of 4.1 μm and a D90 of 11.5 μm. The crystallite size as measured by XRD was approximately 8 nm. It was observed that the crystallite size of the mixed oxide after mechanical treatment remained substantially unchanged.

[0094] Example 1 A solution in 120 mL of deionized water was prepared with 0.1 g of acetic acid to reach a pH of 3.5. A dispersion of mixed oxides was then prepared by adding 80 g of M powder into this 120 mL solution. The pH of the dispersion was 6.2. The pH was further adjusted by dropwise addition of acetic acid (2.5 g of acetic acid at 96 wt%) until a pH of 4.0 was obtained (final weight of dispersion = 202.6 g). The dispersion was homogenized under high stirring with a magnetic stirrer for several hours.

[0095] Then, 116 mL of the homogenous dispersion (167.8 g of dispersion) was placed in the bowl of a laboratory bead mill (500 ml capacity container, bowl diameter 10 cm) containing zirconia beads (605.5 g; average size 350 μm) for wet milling. The dispersion was milled in the bowl with a bead agitator at 1500 rpm for 20 min (which corresponds to a duration of 300 min per kg of oxide).

[0096] Example 2 Example 1 was reproduced under the same conditions as in Example 1.

[0097] Example 3 Example 3 was reproduced under the conditions of Example 1, except that the proportion of mixed oxide M was lower: 25% by weight instead of 39% by weight. Properties of the suspension after milling: D50=70 nm and D90=250 nm. As can be seen in Table 1, a decrease in D50 and D90 was observed for the more diluted suspension. The pH during milling also increased significantly from an initial pH of 4.0 to pH 4.6. The measured viscosity of the suspension was 1s -1 ~1000s -1 at any shear rate of 3 cP.

[0098] Example 4 This example was carried out with a milling time of 40 minutes instead of 20 minutes for Examples 1 and 2. The dispersion was prepared as in Example 1. The slurry was milled in a bowl with bead agitation at 1500 rpm for 40 minutes. An increase in the milling time results in a reduction in particle size: D50=140 nm and D90=590 nm. It should be noted that due to some loss of material on the surface of the bowl and on the beads, the percentage of mixed oxides in the recovered suspension was found to be 36.6%.

[0099] Example 5 This example was carried out with a higher pH of the dispersion than for Example 1. The dispersion was prepared as in Example 1, with a mixed oxide percentage of 36.6% (after milling) and a pH of 6 before milling instead of pH 4. The slurry was milled in a bowl with a bead adiponectin for 40 minutes at 1500 rpm. Compared to Example 4, the higher pH has a slight effect on the D50 and D90, which tend to increase: D50=250 nm and D90=650 nm. The pH during milling also increased significantly from an initial pH of 6.0 to pH 6.6.

[0100] Example 6 The acid used for the preparation of the dispersion was nitric acid instead of acetic acid. A dispersion of mixed oxides was prepared by adding 80 g of M powder into a solution of 120 mL of deionized water plus a few drops of nitric acid. The pH of the dispersion was 5.9. The pH was then adjusted by adding more nitric acid (a total of 1.3 g of 69 wt % nitric acid was used) to obtain a final pH of 4.0. The final weight of the prepared suspension was 201.3 g. The slurry was then milled in a bowl using a bead agitator at 1500 rpm for 40 minutes. Particle characteristics after milling: D50=180 nm and D90=590 nm.

[0101] Example 7 Example 7 was reproduced under the conditions of Example 4, except that the mixed oxide M had a different composition (expressed by weight of oxide): Zr / Ce / La / Y 60.0% / 30.0% / 5.0% / 5.0%. This mixed oxide was prepared by following the recipe of the examples of EP 1527018 B1. The proportion of mixed oxide in the suspension was 36.9% by weight. The final pH was 4.7. The suspension obtained was fluid, like the suspension of Example 4.

[0102] Example 8 Example 8 was reproduced under the conditions of Examples 4 and 7, except that the mixed oxide M had a different composition (expressed by weight of oxide): Zr / Ce / La / Y / Nd 45.0% / 40.0% / 2.0% / 8.0% / 5.0%. This mixed oxide was prepared by following the recipe of the examples of EP 1527018 B1. The proportion of the mixed oxide in the suspension was 37.8% by weight. The suspension obtained was fluid, like the suspension of Example 7.

[0103] Example 9 Example 9 was reproduced under the conditions of Examples 4 and 7, except that the mixed oxide M had a different composition (expressed by weight of oxide): Zr / Ce / La / Nd 63.0% / 30.0% / 1.75% / 5.25%. The proportion of mixed oxide in the suspension was 34.1% by weight. The final pH of the suspension was 4.7. The suspension obtained was fluid, like that of Example 7.

[0104] Example 10 Example 10 was reproduced under the conditions of Examples 4 and 7, except that the mixed oxide M had a different composition (expressed by weight of oxide): Zr / Ce / La / Y 50.0% / 40.0% / 5.0% / 5.0%. The proportion of the mixed oxide in the suspension was 23.0% by weight. The suspension obtained was fluid, like that of Example 7.

[0105] Example 11 Example 11 was reproduced under the conditions of Example 10, except that the proportion of mixed oxide M in the suspension was 19.0% by weight. The suspension obtained was fluid, like that of Example 7.

[0106] Example 12 Example 12 was reproduced under the conditions of Examples 4 and 7, except that the mixed oxide M had a different composition (expressed by weight of oxide): Zr / Ce / La 59.0% / 35.5% / 5.5%. The proportion of mixed oxide in the suspension was 29.0% by weight. The final pH was 4.2. The pH during milling also increased from an initial pH of 3.8 to pH 4.2. The suspension obtained was fluid like the suspension of Example 4.

[0107] Comparative Example 1 The pH of the suspension was different from that in the previous example. A dispersion was prepared as in Example 1, but at a pH of 7.0. It was observed that at this pH the viscosity of the dispersion at about 39 wt. % was much higher than for the suspension of Example 1, so that the dispersion had to be diluted to 34.4 wt. % in order to mill for 30 minutes at 1500 rpm. After 30 minutes the viscosity of the suspension became too high and milling was stopped. It was not possible to reduce the D90 below 1 μm (D90=7.15 μm).

[0108] Comparative Example 2 A suspension at 27.8% by weight was prepared as in Example 1, but without any acid. The pH of the suspension was 8.3. Milling was carried out in a bowl with a bead agitator at 1500 rpm for 30 minutes. After 30 minutes, the viscosity of the suspension became too high and milling was stopped. It was observed that it was not possible to reduce the D90 below 1 μm (D90=10.7 μm).

[0109] Table 1 provides the properties of the suspension. D50 and D90 were measured using a Beckman-Coulter laser particle size analyzer LS13320.

[0110] [Table 1]

Claims

1. A suspension of particles of at least one mixed oxide of zirconium, of cerium, optionally of lanthanum and optionally of at least one rare earth element (RE) other than cerium and lanthanum, in an aqueous liquid medium comprising an acid which is either a mineral acid or a carboxylic acid containing from 2 to 12 carbon atoms, said suspension having the following characteristics: the pH of said suspension is between 2.0 and 7.0 (this latter value being excluded); the proportion of said mixed oxide is between 20.0% and 50.0% by weight; - the specific surface area of ​​the suspension is 15 m when the mixed oxide does not contain La or RE 2 / g, and when the mixed oxide contains La and / or RE, it is 21m 2 / g, said specific surface area being measured after calcination of a solid isolated from said suspension at 1100° C. in air for 4 hours; having Where: the particles of said mixed oxide exhibit a D50 of from 20.0 nm to 900 nm; the proportions of the elements Ce, Zr, La and RE, expressed by weight of oxide relative to the mixed oxide, are as follows: from 20.0% to 55.0% by weight of cerium; up to 10.0% by weight of lanthanum; up to 15.0% by weight of rare earth elements (RE) other than cerium and lanthanum; The remainder as zirconium That is, a suspension.

2. particles of at least one mixed oxide of zirconium, of cerium, optionally of lanthanum and optionally of at least one rare earth element (RE) other than cerium and lanthanum; ・Aqueous liquid medium; An acid that is either a mineral acid or a carboxylic acid containing from 2 to 12 carbon atoms. A suspension comprising: The suspension has the following characteristics: the pH of said suspension is between 2.0 and 7.0 (this latter value being excluded); the proportion of said mixed oxide is between 20.0% and 50.0% by weight; - the specific surface area of ​​the suspension is 15 m when the mixed oxide does not contain La or RE 2 / g, and when the mixed oxide contains La and / or RE, it is 21m 2 / g, said specific surface area being measured after calcination of a solid isolated from said suspension at 1100° C. in air for 4 hours; having Where: the particles of said mixed oxide exhibit a D50 of from 20.0 nm to 900 nm; the proportions of the elements Ce, Zr, La and RE, expressed by weight of oxide relative to the mixed oxide, are as follows: from 20.0% to 55.0% by weight of cerium; up to 10.0% by weight of lanthanum; up to 15.0% by weight of rare earth elements other than cerium and lanthanum; The remainder as zirconium That is, a suspension.

3. 3. Suspension according to claim 1 or 2, wherein the mixed oxide also contains the element hafnium.

4. 4. Suspension according to claim 1, wherein the mixed oxide comprises the element hafnium in a proportion not greater than 2.5% by weight, this proportion being expressed as the weight of oxide relative to the mixed oxide.

5. The mixed oxide is the elements Ce and Zr; or the elements Ce, Zr and La; or - the elements Ce, Zr, La and at least one RE A suspension according to any one of claims 1 to 4 based on

6. 6. Suspension according to any one of claims 1 to 5, wherein the elements Ce and Zr, La or RE (if present), and Hf (if present) are present in the mixed oxide as oxides.

7. The proportion of cerium in the mixed oxide is - 30.0% to 55.0% by weight; or - 30.0% to 45.0% by weight; or - 25.0% to 35.0% by weight The suspension according to any one of claims 1 to 6,

8. 8. Suspension according to claim 1, wherein the proportion of lanthanum in the mixed oxide is between 1.0% and 10.0% by weight.

9. 9. Suspension according to claim 1, wherein the total proportion of non-cerium and non-lanthanum rare earth elements in the mixed oxide is not more than 10.0% by weight.

10. The suspension according to any one of claims 1 to 9, wherein the pH is from 3.0 to 6.

0.

11. 11. Suspension according to any one of the preceding claims, wherein the proportion of the mixed oxides is between 25.0% and 50.0% by weight.

12. The acid is nitric acid or an acid of formula R 1 -COOH (in the formula, R 1 A suspension according to any one of claims 1 to 11, wherein the carboxylic acid is a carboxylic acid of the formula:

13. 13. The suspension according to any one of claims 1 to 12, wherein the acid is a carboxylic acid selected in the group consisting of acetic acid, propionic acid, butanoic acid, hexanoic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, maleic acid and citric acid.

14. The suspension according to any one of claims 1 to 13, wherein the acid is acetic acid.

15. 12. The suspension according to any one of claims 1 to 11, wherein the acid is a carboxylic acid containing at least one functional group other than COOH, which may be selected in the group consisting of OH, C=O, aldehyde and ester groups.

16. 16. Suspension according to any one of the preceding claims, wherein the suspension does not contain any metal oxide other than the mixed oxide, said metal oxide being defined as an oxide of at least one metal.

17. 16. Suspension according to any one of claims 1 to 15, wherein the suspension does not comprise any metal oxide other than said mixed oxide, said metal oxide being defined as an oxide of at least one metal selected in the group consisting of Al, Zr or Ti.

18. At least 35 meters 2 18. The suspension according to claim 1, wherein the suspension exhibits a specific surface area (BET) of 1000° C. / g, said specific surface area being measured after calcination at 1000° C. in air for 4 hours of a solid isolated from the suspension.

19. The specific surface area of ​​the suspension is determined by the following steps: (i) a solid is isolated from said suspension; (ii) the solid is then dried in air at 500° C. for 1 hour; (iii) calcining the dried solid in air at 1100° C. for 4 hours or at 1000° C. for 4 hours.

19. The suspension of any one of claims 1 to 18, wherein the solid is isolated by a method comprising:

20. The suspension exhibits a total pore volume (TPV) of greater than 0.50 mL / g, and the TPV has been determined by the steps of: (i) a solid is isolated from said suspension; (ii) The solid is then dried in air at 500° C. for 1 hour.

20. The suspension according to any one of claims 1 to 19, measured by mercury porosimetry on the solid isolated by a process comprising:

21. The suspension has a pore volume (PV) measured by mercury porosimetry for pores having a diameter of less than 300 nm that is greater than 0.15 mL / g. 0~300nm ), and PV 0~300nm But the following steps: (i) a solid is isolated from said suspension; (ii) The solid is then dried in air at 500° C. for 1 hour.

21. The suspension according to any one of claims 1 to 20, as measured by mercury porosimetry on the solid isolated by a method comprising:

22. 22. The suspension according to any one of claims 1 to 21, wherein D50 is from 20.0 nm to 400.0 nm.

23. 23. A suspension according to any one of claims 1 to 22, wherein the particles exhibit a D90 of less than 1000 nm.

24. 24. A suspension according to any one of the preceding claims, wherein the particles exhibit a D90 between 50 nm and 1000 nm.

25. 25. A suspension according to any one of the preceding claims, wherein the particles exhibit a D90 between 50 nm and 500 nm.

26. 26. A suspension according to any one of claims 1 to 25, having a D90 of less than 200 nm.

27. 27. A suspension according to any one of claims 1 to 26, having a D90 of less than 100 nm.

28. After sintering in air at 1100° C. for 4 hours, the specific surface area is 40 m 2 The suspension according to any one of claims 1 to 27, wherein the viscosity is 0.1 to 1.0 g / g or less.

29. The suspension exhibits a viscosity, V, of less than 1000 cP, where V is measured at 20° C. using a rheometer with a cylindrical Couette geometry, where the sample is first heated to 1 s over a 5 minute ramp time. -1 From 100s -1 and then subjected to an increasing shear rate of 100 s for 5 min. -1 From 1s -1 and V is increased by 10 s during the shear rate decrease. -1 29. A suspension according to any one of claims 1 to 28, which corresponds to a value measured at a shear rate of

30. A suspension according to any one of the preceding claims, wherein the aqueous liquid medium is water.

31. A suspension according to any one of the preceding claims, wherein the aqueous liquid medium comprises at least one other liquid that is miscible with water.

32. 32. A suspension according to any one of the preceding claims having a D50 of from 20 nm to 100 nm and a D90 of from 50 nm to 120 nm.

33. 32. A suspension according to any one of the preceding claims having a D50 of from 40 nm to 100 nm and a D90 of from 50 nm to 120 nm.

34. Weight ratio ZrO 2 / CeO 2 34. The suspension according to any one of claims 1 to 33, wherein is greater than 1.

0.

35. A method for preparing a suspension according to any one of claims 1 to 34, wherein a dispersion comprising a mixed oxide M dispersed in an aqueous liquid medium comprising an acid is subjected to a mechanical treatment to reduce the size of the particles of said mixed oxide.

36. The specific surface area of ​​the mechanically treated mixed oxide M is 17m if the mixed oxide M does not contain La or RE 2 / g; and 25m when the mixed oxide contains La and / or RE 2 / g or more, 36. The method according to claim 35, wherein the specific surface area is measured after calcination of the mixed oxide in air at 1100°C for 4 hours.

37. 37. The method according to claim 35 or 36, wherein the mechanical treatment is based on the attrition of the mixed oxide with beads that are brought into motion in contact with the solid.

38. Use of a suspension according to any one of claims 1 to 34 for the preparation of cGPF.

39. A process for the preparation of a catalytic composition, wherein the suspension according to any one of claims 1 to 34 is contacted with at least one inorganic material and optionally at least one PGM.

40. 40. The method of claim 39, wherein the inorganic material is selected from the group consisting of optionally doped alumina, titanium oxide, cerium oxide, zirconium oxide, silica, spinels, zeolites, silicates, crystalline silicon-aluminum phosphates and crystalline aluminum phosphates.

41. 41. The method of claim 39 or 40, comprising the addition of a liquid.

Citation Information

Patent Citations

  • A highly reducible composition made from nanometer cerium oxide on a support, a method for preparing it, and its use as a catalyst.

    JP2010501346A

  • Inorganic composite oxide and method for producing the same

    JP2017502917A

  • Automotive catalyst with supported palladium in alumina-free layer

    JP2018513781A

  • Zirconia-based aqueous NP dispersions for use in filter substrate coatings

    JP2022519448A

  • Cerium-and zirconium-based mixed oxides

    WO2017185224A1